INTERNALISASI NILAI PEDULI LINGKUNGAN SISWA SEKOLAH DASAR MELALUI PENGELOLAHAN SAMPAH PLASTIK BERBASIS BANK SAMPAH SEKOLAH - Salwa Tsabitah Hummaira; Anna Maria Oktaviani; Empat Sunisti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Environmental problems caused by plastic waste have become a serious challenge in achieving sustainable development, including in the school environment. One strategic effort to address this issue is by instilling environmental care values from an early age through educational programs. This study aims to analyze the internalization of environmental care values among elementary school students through plastic waste management based on the School Waste Bank program. The research employed a qualitative approach with a descriptive research design. Data were collected using a literature study by reviewing and analyzing various relevant Indonesian scientific journals, books, and research reports related to environmental education, character education, and school waste bank implementation. The results of the study indicate that the School Waste Bank program plays an effective role in internalizing students’ environmental care values through three interconnected domains: cognitive, affective, and psychomotor. Cognitively, students gain an understanding of the environmental impacts of plastic waste and the importance of waste management. Affectively, the program fosters attitudes of responsibility, discipline, and empathy toward the environment. Psychomotorically, students develop practical skills and habitual behaviors in sorting, recycling, and reusing plastic waste. Furthermore, the School Waste Bank contributes to creating a sustainable school culture that supports character education. Therefore, plastic waste management based on the School Waste Bank can serve as an effective educational medium in shaping environmentally responsible character among elementary school students.